When the bottom line is faithfulness : management of Christian service organizations - Jeavons, Thomas (Philanthropic studies., 1994)
Religious service organizations play a central role in philanthropy in the United States. As with their secular counterparts, society expects that these organizations will be "values-expressive," idealistic as well as pragmatic, upholding and promoting an identifiable set of social and moral values as well as providing particular services. For religious philanthropies, these societal concerns create a distinctive set of management issues